2015
DOI: 10.5194/esurf-3-35-2015
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of bedload transport in Swiss mountain rivers using the model sedFlow: proof of concept

Abstract: Abstract.Fully validated numerical models specifically designed for simulating bedload transport dynamics in mountain streams are rare. In this study, the recently developed modelling tool sedFlow has been applied to simulate bedload transport in the Swiss mountain rivers Kleine Emme and Brenno. It is shown that sedFlow can be used to successfully reproduce observations from historic bedload transport events with plausible parameter set-ups, meaning that calibration parameters are only varied within ranges of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…To ensure this approximation, Eulerian forward approaches require very small time steps, especially for fast processes. This can be problematic when a relatively fast process, such as the routing of water, is combined with a relatively slow process, such as bedload 18 F. U. M. Heimann et al: The bedload transport model sedFlow Heimann et al (2015) transport including bed level adjustments. The water routing requires small time steps and thus calculation times that may be orders of magnitude too long and slow from the perspective of bedload dynamics.…”
Section: Flow Routingmentioning
confidence: 99%
See 3 more Smart Citations
“…To ensure this approximation, Eulerian forward approaches require very small time steps, especially for fast processes. This can be problematic when a relatively fast process, such as the routing of water, is combined with a relatively slow process, such as bedload 18 F. U. M. Heimann et al: The bedload transport model sedFlow Heimann et al (2015) transport including bed level adjustments. The water routing requires small time steps and thus calculation times that may be orders of magnitude too long and slow from the perspective of bedload dynamics.…”
Section: Flow Routingmentioning
confidence: 99%
“…Heimann et al (2015) have demonstrated that, despite their simplicity, the implemented hydraulic concepts (Fig. 2) appear to be sufficient for a realistic integrated representation of bedload transport processes.…”
Section: Flow Routingmentioning
confidence: 99%
See 2 more Smart Citations
“…These data were used as benchmarks for the simulation. In this way, an attempt was made to overcome the lack of field validation that is frequently a shortcoming in similar studies (e.g., [37,38]). …”
Section: Model Parameterization/validationmentioning
confidence: 99%